2015
DOI: 10.4172/2157-7439.1000335
|View full text |Cite
|
Sign up to set email alerts
|

Heat Dissipation of Hybrid Iron Oxide-Gold Nanoparticles in an Agar Phantom

Abstract: Hybrid iron oxide-gold nanoparticles (HNPs) have shown potential in cancer therapy as agents for tumour ablation and thermal switches for targeted drug release. Heat generation occurs by exploitation of the surface plasmon resonance of the gold coating, which usually occurs at the maximum UV absorption wavelength. However, lasers at such wavelength are often expensive and highly specialised. Here, we report the heating and monitoring of heat dissipation of HNPs suspended in agar phantoms using a relatively ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The presence of Au provides two main advantages: (i) a wellknown and versatile platform for surface functionalization, the gold−thiol chemistry, and (ii) gold adds plasmonic features to the superparamagnetic NPs that can be exploited for multimodal imaging, such as contrast for CT (computed tomography) and SERS (surface enhanced Raman spectroscopy) imaging in vivo, 13 and photothermal therapy. 17 Our primary motivation is to develop magnetic nanoparticles that can be used as nontoxic, cell-degradation resistant MRI contrast agents, e.g., for long-term follow-up studies of transplanted stem cells or for in vitro and in vivo studies to follow tumor growth of NP-loaded tumor cells. The magnetoresponsive Au/Fe NPs described in this work combine the capability of cell internalization shown by mixed-ligand gold nanoparticles 5,18,19 with magnetic features.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The presence of Au provides two main advantages: (i) a wellknown and versatile platform for surface functionalization, the gold−thiol chemistry, and (ii) gold adds plasmonic features to the superparamagnetic NPs that can be exploited for multimodal imaging, such as contrast for CT (computed tomography) and SERS (surface enhanced Raman spectroscopy) imaging in vivo, 13 and photothermal therapy. 17 Our primary motivation is to develop magnetic nanoparticles that can be used as nontoxic, cell-degradation resistant MRI contrast agents, e.g., for long-term follow-up studies of transplanted stem cells or for in vitro and in vivo studies to follow tumor growth of NP-loaded tumor cells. The magnetoresponsive Au/Fe NPs described in this work combine the capability of cell internalization shown by mixed-ligand gold nanoparticles 5,18,19 with magnetic features.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The HNP preparation and characterisation has been reported previously [21,22] along with their ability to undergo triggered heating upon laser irradiation in agar phantoms [17,34], in vitro and in situ in tumour bearing mouse cadavers [35,36]. Drug attachment was carried out at three drug:HNP weight ratios (5:1, 2.5:1 and 1:1 based on Fe weight of HNP) for all four bisnaphthalamide based drugs.…”
Section: Hnp-drug Conjugation and Characterisationmentioning
confidence: 99%
“…In order to exploit the thermo-responsive properties of these formulations, laser irradiation was used. Extensive previous studies have been carried out in order to optimize the laser treatment duration in order to achieve temperatures that are likely to initiate drug release without adverse effects to tissue [34,35]. Figure 6 A 1 shows a tumour excised from a control group mouse.…”
Section: In Vivo Evaluationmentioning
confidence: 99%
“…Previously we reported the controllable heating capacity and resultant dissipation aer irradiation of HNPs in agar phantoms at varied concentrations. 21 These studies suggested that the HNPs used (50 nm) would be useful for stimuli responsive drug release as their heating could be controlled via alteration of irradiation time and concentration. In order for HNPs to be used to thermally trigger drug release it is important that their temperature rise is not sufficient to cause any thermal degradation of drug or widespread heat dissipation at high temperatures which would affect healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the thermal potential and heat dissipation of HNPs for stimuli responsive drug delivery have been reported, however the majority of these have been either been carried out using computer modelling 22 or in the use of agar phantoms 21,23 and little studies have shown heating abilities aer cellular internalization. Whilst gel phantoms are designed to mimic physiological tissue there is an increasing need to fully understand the heating ability and effect on surroundings experienced aer irradiation in more realistic conditions either in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 99%